Uji Aktivitas Antibakteri Fraksi N-Heksan Kayu Bajakah (Uncaria tomentosa) Terhadap Bakteri Escherichia coli: Uji Aktivitas Antibakteri Fraksi N-Heksan Kayu Bajakah (Uncaria tomentosa) Terhadap Bakteri Escherichia coli - Firda Nirmalasari; Kunti Nastiti; Mia Audina (LPPM Universitas Sari Mulia, 2023)
Background: Diarrhea is an infectious disease which is still the highest case in Indonesia. Drug therapy currently used as the drug of choice in diarrheal diseases is chloramphenicol class of antibiotics. It is known that treatment using chemicals is more prone to causing unwanted side effects. To deal with this problem, efforts need to be made in the form of exploring the latest therapies to kill bacteria. New therapeutic sources that can be found from plants that have the potential as antibacterial. Objective: This study aimed to determine the antibacterial activity of the n-hexane fraction in the extract of bajakah wood (Uncaria tomentosa) by testing its inhibition and killing power by observing the minimum inhibition and minimum killing of Escherichia coli bacteria. Methods: This study used a true experimental type of research in the manufacture of extracts using the maceration method and the antibacterial activity test method used the disc diffusion method and continued with the dilution method with concentrations of 100,50,25,12,5, and 6,25 ppm and the inhibition concentration was determined. minimum and minimum kill concentration. Analysis of this data using the Kruskal-Wallis and Mann Whitney test. Results: The results of the antibacterial activity of the n-hexane fraction of bajakah wood (Uncaria tomentosa) against Escherichia coli bacteria with an inhibition zone of 7.72 mm. The results of the analysis showed that there was a significant difference with a p value of 0.005 at Kruskal-Wallis and at Mann Whitney showing a p value of 0.05. minimum inhibitory concentration (MIC) showed clarity at a concentration of 50 ppm. Conclusion: The n-hexane fraction of pirated wood against Escherichia coli bacteria has a minimum inhibitory concentration (MIC) at a concentration of 50 ppm. However, it does not have a minimum kill concentration (MKC).